Minimizing risk of customized titanium mesh exposures - a retrospective analysis - Amely Hartmann; Marcus Seiler (BMC, 2020)
Abstract Background Recommendations for soft tissue management associated with customized bone regeneration should be developed. The aim of this study was to evaluate a new protocol for customized bone augmentation in a digital workflow. Methods The investigators implemented a treatment of three-dimensional bone defects based on a customized titanium mesh (Yxoss CBR®, ReOSS, Filderstadt, Germany). Patients and augmentation sites were retrospectively analysed focussing on defect regions, demographic factors, healing difficulties and potential risk factors. An exposure rate was investigated concerning surgical splint application, A®- PRF and flap design. Results In total, 98 implants could be placed. Yxoss CBR® was removed after mean time of 6.53 ± 2.7 months. Flap design was performed as full flap preparation (27.9%), full flap and periosteal incision (39.7%), periosteal incision (1.5%), poncho/split flap (27.9%) and rotation flap (2.9%). In 25% of the cases, exposures of the meshes were documented. Within this exposure rate, most of them were slight and only punctual (A = 16.2%), like one tooth width (B = 1.5%) and complete (C = 7.4%). A®- PRF provided significantly less exposures of the titanium meshes (76.5% no exposure vs. 23.5% yes, p = 0.029). Other parameters like tobacco abuse (p = 0.669), diabetes (p = 0.568) or surgical parameters (mesh size, defect region, flap design) did not influence the exposure rate. Surgical splints were not evaluated to reduce the exposure rate (p = 0.239). Gender (female) was significantly associated with less exposure rate (78,4% female vs. 21.6% male, p = 0.043). Conclusions The results of this study suggest that the new digital protocol including patient-specific titanium meshes, resorbable membranes and bone grafting materials was proven to be a promising technique. To improve soft tissue healing, especially A®-PRF should be recommended.